Hubungan Pengetahuan Anemia Dengan Asupan Makanan Sumber Fe Pada Mahasiswi Fakultas Ilmu Kesehatan UMS - Mardhani, Sheila Dwi; Widiyaningsih, Endang Nur (Prosiding University Research Colloquium, 2022)
Introduction: Female student is part of the young women who have a risk of anemia. Anemia that usually occurs in adolescent girls is the result of a lack of Fe intake in the body. The intake of Fe into the body is influenced by various things, one of which is knowledge about anemia which can impact the consumption of food sources of Fe. Objective: This study aims to determine the correlation between knowledge of anemia and intake of food sources of Fe in UMS health science students. Method: The design of this study was observational with a cross-sectional approach. The population of this research is the 3rd semester students of the health sciences faculty of UMS. The number of samples is 87 respondents. The sampling technique used is accidental sampling. The instruments in this study were the anemia knowledge questionnaire and the SQ-FFQ Form. Statistic test used is Rank Spearman. Result: The results showed that as many as 53 respondents (61%) had a good level of knowledge and most of the respondents had a low-level intake of Fe sources, as much 77 respondents (88.5%). The results of the Spearman Rank test showed the ? value of 0.814 (> 0.05) had no correlation between knowledge and intake of food sources of Fe in UMS health science students. Consclusion: A good level of knowledge is not sure to be able to change a person's eating habits, because a level of knowledge is not a main influenced factor of a person's eating habits but also environmental, socio-economic, cultural, occupational, and age factors.